Durable response to CAR T is associated with elevated activation and clonotypic expansion of the cytotoxic native T cell repertoire - Giulia Cheloni; Dimitra Karagkouni; Yered Pita-Juarez; Daniela Torres; Eleni Kanata; Jessica Liegel; Zachary Avigan; Isabella Saldarriaga; Georges Chedid; Kathrine Rallis; Brodie Miles; Gayatri Tiwari; et al. (Nature Communications)
Abstract While Chimeric Antigen Receptor (CAR) T cell therapy may result in durable remissions in recurrent large B cell lymphoma, persistence is limited and the mechanisms underlying long-term response are not fully elucidated. Using longitudinal single-cell immunoprofiling, here we compare the immune landscape in durable remission versus early relapse patients following CD19 CAR T cell infusion in the NCT02348216 (ZUMA-1) trial. Four weeks post-infusion, both cohorts demonstrate low circulating CAR T cells. We observe that long-term remission is associated with elevated native cytotoxic and proinflammatory effector cells, and post-infusion clonotypic expansion of effector memory T cells. Conversely, early relapse is associated with impaired NK cell cytotoxicity and elevated immunoregulatory cells, potentially dampening native T cell activation. Thus, we suggest that durable remission to CAR T is associated with a distinct T cell signature and pattern of clonotypic expansion within the native T cell compartment post-therapy, consistent with their contribution to the maintenance of response.